Eating pathology and associations with long‐term changes in weight and quality of life in the longitudinal assessment of bariatric surgery study. Issue 12 (6th December 2018) - Devlin, Michael J.; King, Wendy C.; Kalarchian, Melissa A.; Hinerman, Amanda; Marcus, Marsha D.; Yanovski, Susan Z.; Mitchell, James E.
Abstract: Objective: This study examines the course of eating pathology and its associations with change in weight and health‐related quality of life following bariatric surgery. Method: Participants ( N = 184) completed the eating disorder examination‐bariatric surgery version (EDE‐BSV) and the medical outcomes study 36‐Item short form health survey (SF‐36) prior to and annually following Roux‐en‐Y gastric bypass (RYGB) or laparoscopic adjustable gastric banding (LAGB) for up to 7 years. Results: The prevalence of ≥ weekly loss of control (LOC) eating, picking/nibbling, and cravings declined post‐RYGB and remained lower through 7 years (LOC: 5.4% at Year‐7 vs. 16.2% pre‐RYGB, p = .03; picking/nibbling: 7.0% vs. 32.4%, p < .001; and cravings: 19.4% vs. 33.6%, p = .02). The prevalence of picking/nibbling was significantly lower 7 years following LAGB vs. pre‐LAGB (29.4% vs 45.8%, p = .049), while cravings ( p = .13) and LOC eating ( p = .95) were not. EDE‐BSV global score and ratings of hunger and enjoyment of eating were lower 7 years following both RYGB and LAGB versus pre‐surgery ( p 's for all <.05). LOC eating following RYGB was associated with less long‐term weight loss from surgery ( p < .01) and greater weight regain from weight nadir ( p < .001). Higher post‐surgery EDE‐BSV global score was associated with less weight loss/greater regain (both p < .001) and worsening/less improvement from surgery in the SF‐36 mental component summary scores ( p < .01). Discussion: Initial improvements in eating pathology following RYGB and LAGB were sustained across 7 years of follow‐up. Individuals with eating pathology post‐RYGB, reflected by LOC eating and/or higher EDE‐BSV global score, may be at risk for suboptimal long‐term outcomes.